Determinación de la calidad de Pasto Rye Grass y su relación a las categorías animales en la Hacienda Alelí del Cantón Pillaro - Dután Chimbo, Byron Raúl (2019)
he objective of this project was to carry out research that was carried out at the “ALELI” farm located in the Province of Tungurahua, Píllaro Canton, whose geographical location is 1o 8´49, 47¨ South latitude and 78o 32´ 50,137¨ de west longitude at a height of 2853.3 meters above sea level. The quality of ryegrass grass was determined in relation to dairy cows by quantifying the animal load and nutrients of the grass. To establish intensive rational grazing, a bromatological analysis was carried out to determine the nutritional status of ryegrass grass in the same way as the percentage of Dry Matter, Metabolizable Energy, Neutral Detergent Fiber, Acid Detergent Fiber, protein and minerals from ryegrass grass. In order to establish the relationship of the amount of nutrients in relation to the animals present in the research site. In relation to pasture production per hectare, an amount of 2000 Kg / ms / ha was determined. In each grazing period; The average consumption capacity of animals is 14.84 kg / ms / day, energy is 42.49 mcal / MS / day, protein 4303.06 gr / day, calcium with 59.36gr / day and phosphorus of 160.27gr / day. What allows us to determine under NRC standards that animals that produce 18 liters of milk meet the requirements of energy, protein and phosphorus with the unique consumption of grass, there is a deficiency of 16.44 g / day of calcium in the diet . The categories of the animals are divided in relation to their weight and / or physiological condition, which determines that for all subsequent categories to the animals that produce milk the nutritional requirements under study are met since there is a difference in the requirements of the same. The assessment of the quality and quantity of the grass that the animals consume in relation to the nutrients they possess allows for a more efficient grazing that meets the provision of the necessary nutrients for the various categories in the animals and their production.